Effects of the Announcement of the Covid-19 Status Change on Stock Prices in the LQ45 Index of the Indonesia Stock Exchange in the Period of February - August 2020 - Irni Yunita; Muhammad Farid Pratama; Roderta Cahya Diputra; Graciano Andre Damiao Maia (Budapest International Research and Critics University, 2022)
This study aims to show the response of the stock price before and after the announcement of the Covid-19 status change from endemic to pandemic by WHO on March 12th, 2020. This research can be measured using abnormal returns and trading volume activity with the event study approach. The samples in this study are the shares of the LQ45 index issuers in the period of February 2020 - July 2020 selected using purposive sampling technique. In this study, the period used was 5 days before the announcement, 1 day at the time of the announcement, and 5 days after the announcement. The results of this study show that there was no significant difference on abnormal returns before and after the announcement of the Covid-19 status change towards the LQ45 stock index. Furthermore, there was no significant difference on trading volume activity before and after the announcement of the Covid-19 status change towards the LQ45 stock index.